Molecular Detection of Pseudomonas Aeruginosa Isolated from Different Clinical Cases and Test Antibiotics Sensitivity on the Bacterial Growth - Duaa Adilabdulhady, Hadaf Mahdi Kadhim (Pakistan Journal of Medical & Health Sciences, 2022)
150 samples were collected from different clinical causes of hospitals in Al-Diwaniyah city. All samples were cultured on blood agar and Maconkey agar medium and incubated for 24 hat 37°C. The results showed 112 (74.6%) bacterial growth. Initially, identification of the bacterial isolates were carried out viabiochemical tests, 25 isolates Pseudomonasaeruginosa were detected. Identity was confirmed by polymerase chain reaction (PCR) targeting the areE genewith size 498pb. This bacterium was isolated from burn infection 30% and wound infection 20%, while it was isolated from Respiratorytract 16.6%. The antibiotics susceptibilitytest for 16 bacterial isolates have been tested. It has been found that the bacterial isolates were resistance 100% for Ampicillin, Amoxicillin, Piperacillin, Cefotaxime and Cefepim and 18.75% forMeropenem. While they were sensitive 100% for Amikacin. Keywords: antibiotics, areE gene, Pseudomonas aeruginosa, PCR.